Pelaksanaan Pengadaan Sumur Bor Oleh Cipta Karya Menurut Peraturan Presiden Nomor 12 Tahun 2021 Tentang Perubahan Atas Peraturan Presiden Nomor 16 Tahun 2018 Tentang Pengadaan Barang/Jasa Pemerintah: Studi Di Desa Wakan Kecamatan Jerowaru, Kabupaten Lombok Timur - Jorgi, Tomas; Wagian, Diangsa (Fakultas Hukum Universitas Mataram, 2024)
This research aims to determine the procedures for procuring goods/services by the government through service providers and to discover the obstacles/obstacles to its implementation. This research focuses on procuring drilled wells in Wakan Village, Kec. Jerowaru, Kab. East Lombok, with empirical research, takes data from the field and analyzes it qualitatively. This research shows that procurement facts in the field still need to be improved because implementing this procurement is not under existing regulations. This procurement is also not under Presidential Regulation No. 12 of 2021 concerning Amendments to Presidential Regulation No. 16 of 2018 concerning implementing Government Procurement of Goods/Services. This procurement is also not under the agreement’s procurement principles, ethics, and general principles. In procuring government goods/services in the form of drilling wells, researchers found obstacles/obstacles in implementation, namely, lack of water resources, lack of technological sophistication, and geographical location.